DASAR HUKUM NOTARIS DALAM PEMBUATAN SURAT KETERANGAN WARIS - Saputra, Gede Afriliana; Ariani, I Gusti Ayu Agung; Palguna, I Dewa Gede (Acta Comitas : Jurnal Hukum Kenotariatan, 2016)
There is no provision that explicitly regulate the notaries in making of a declaration of inheritance for the European, Chinese or Tionghoa, Foreign Easterners (except for Arabs Moeslems), although there has been the Regulation of the Minister of State for Agrarian Affairs / Head of National Land Agency Number 3 Year 1997 on the Implementation of the Provisions of the Government Regulation No. 24 of 1997 on Registration, that stipulates about the Certificate of Inheritance made ??by the public notary. However, this Regulation of the Minister of State is not classified as any type of legislation. In addition to being included in the category Regulation of the Minister of State for Agrarian Affairs / Head of National Land Agency Number 3 Year 1997 on the Implementation of the Provisions of the Government Regulation No. 24 of 1997 on Registration made ??by the Minister of state for agrarian affairs applies only internally, in the sense that the decision is not binding general. Therefore, the researcher will answer and analyze the legal basis for the making of a notary certificate of inheritance, and identify the legal nature of the certificate of inheritance.
Keywords: Legal Basis, Notary, Certificate of Inheritance